Under the Stars : A Novel - Williams, Beatriz (New York : Ballantine Books, 2025)
"When a daughter and her famous mother return to Winthrop Island to confront their complicated past, they discover a secret trove of paintings that connect them to a mysterious woman who vanished on a luxury steamship two centuries earlier. From the New York Times bestselling author of Husbands & Lovers comes an epic tale of family legacy, love, and truths that echo down generations"-- Provided by publisher.
new book 2025 summer.
Keywords: Islands; Suspects (Criminal investigation); Painting; Detective and mystery stories; Novels; Mothers and daughters; Children of celebrities; Shipwrecks; Secrecy; Domestic fiction; Fiction; Actresses; Steamboats; New England; Detective and mystery fiction; Domestic fiction; Novels; Fiction; Detective fiction; Mystery fiction